Embedding young people's participation in health services : new approaches - Brady Louca-Mai (Policy Press, 2020)
This book explores how young people's participation can be inclusively and sustainably embedded into health services. Using rich case studies of participation in practice, Brady presents a new evidence-based framework to support policymakers and practitioners to embed young people's participation more effectively in healthcare practice.